Asthma, from mild to severe, is an independent prognostic factor for mild to severe Coronavirus disease 2019 (COVID‐19). (11th February 2022) - Kwok, Wang Chun; Tam, Anthony Raymond; Ho, James Chung Man; Lam, David Chi Leung; Tam, Terence Chi Chun; Chan, King Pui Florence; Wang, Julie Kwan Ling; Ip, Mary Sau Man; Hung, Ivan Fan Ngai
Abstract: Background: Chronic illnesses were reported to be poor prognostic factors associated with severe illness and mortality in Coronavirus disease 2019 (COVID‐19) infection. The association with asthma, however, is limited and controversial, especially for mild asthma. Methods: A territory wide retrospective study was conducted to investigate the association between asthma and the prognosis of COVID‐19. All patients with laboratory confirmed in Hong Kong for COVID‐19 from the 23 January to 30 September 2020 were included in the study. Severe diseases were defined as those who develop respiratory complications, systemic complications, and death. Results: Among the 4498 patients included in the analysis, 165 had asthma, with 141 having mild asthma. Patients with asthma were significantly more likely to require invasive mechanical ventilation (incidence = 17.0% odds ratio [OR] = 4.765, p  < 0.001), oxygen therapy (incidence = 39.4%, OR = 3.291, p  < 0.001), intensive care unit admission (incidence = 21.2%, OR = 3.625, p  < 0.001), and systemic steroid treatment (incidence = 34.5%, OR = 4.178, p  < 0.001) and develop shock (incidence = 16.4%, OR = 4.061, p  < 0.001), acute kidney injury (incidence = 6.1%, OR = 3.281, p  = 0.033), and secondary bacterial infection (incidence = 56.4%, OR = 2.256, p  < 0.001). They also had significantly longer length of stay. Similar findings were also found in patients with asthma of the Global Initiative for Asthma (GINA) steps 1 and 2 upon subgroup analysis. Conclusions: Asthma, regardless of severity, is an independent prognostic factor for COVID‐19 and is associated with more severe disease with respiratory and systemic complications. Abstract : Both mild and severe asthma are independent prognostic factors for Coronavirus disease 2019 (COVID‐19). They are associated with more severe disease with respiratory and systemic complications.